2020
DOI: 10.31557/apjcp.2020.21.7.1891
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Functional Assessment of Cancer Therapy with Cervical Cancer Subscale (FACT-CX) for Quality of Life in Thai Patients Prior to Chemoradiotherapy

Abstract: Objective: Cervical cancer is the second most common cancer in Thailand. For cervical cancer, there is no cancer specific quality of life questionnaire. This study aims to develop and validate Thai FACT-CX. Methods: The cross-sectional study included all women aged ≥18 years with stage IB2-IIIB who planned to undergo chemoradiotherapy. Those who did not understand Thai language, had other cancers (except for skin cancer), were diagnosed with impaired cognition and/or ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
(14 reference statements)
2
1
0
Order By: Relevance
“…Our study found that patients with cervical precursor lesions and cancer aged 40-59 years had the lowest HRQoL utility and VAS scores. This result was consistent with studies in Korea [23] and Thailand [24]. Previous research indicates that incidence of cervical cancer is highest in those aged 40-59 years [17].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our study found that patients with cervical precursor lesions and cancer aged 40-59 years had the lowest HRQoL utility and VAS scores. This result was consistent with studies in Korea [23] and Thailand [24]. Previous research indicates that incidence of cervical cancer is highest in those aged 40-59 years [17].…”
Section: Discussionsupporting
confidence: 93%
“…Our ndings indicate that low household income is associated with lower HRQoL utility scores, a nding consistent with study results in Thailand [24]. This association of household income with HRQoL of patients with cervical precursor lesions and cancer suggests wealthier patients may be more conscious about and able to spend money to promote their health.…”
Section: Discussionsupporting
confidence: 90%
“…The side effects of long-term radiotherapy and multi cycle chemotherapy bring great pain and psychological trauma to patients [ 25 ]. Moreover, during waiting for radiotherapy, fear and misunderstanding of radiotherapy will cause anxiety, which causing physical symptoms and emotional distress will affect the health-related quality of life of patients [ 26 ]. The health-related quality of life of younger patients is also better than that of older patients, which may be related to the better physical function of younger patients [ 27 ].…”
Section: Discussionmentioning
confidence: 99%